Compreendendo padrões e processos em metacomunidades de peixes em uma estrutura dendrítica - Rezende, Breno Laio Medeiros de (2019)
Metacommunity Ecology is a field in which the knowledge of patterns and particularly their process remains a challenge. Nowadays, there are four major concepts to explain metacommunity patterns, they are: i) neutral theory, ii) species sorting, iii) mass effects, and iv) patch dynamics. Lotic ecosystems are important systems that incorporate metacommunity theoretical conflicts. Studies carried out diverge on the importance of environmental and spatial variables, and they do not include dispersal resistance factors. The goal of the present work is to understand determinant mechanisms of fish species composition in lotic metacommunities as well as the degree of importance between environmental and spatial variables. Dispersals costs were defined using slope, elevation differences, drainage network distances, and hydroelectric dams. In addition, asymmetric beta diversity was calculated to evaluate nestedness between upstream and downstream communities. Generalized Dissimilarity Model (gdm) was applied to analyze symmetric dissimilarities due to its ability to include multiple variables and because it includes non-constant rate of compositional turnover along gradients. Asymmetric dissimilarities were analyzed using Mantel tests. The predictor variables in the generalized dissimilarity model explained 22.26% of compositional dissimilarity and the most important predictor was elevation. Nestedness between downstream and upstream communities was not detected. The present work supports the importance of environmental filters in the structure of lotic fish metacommunity.